2017
DOI: 10.1039/c7ra08737c
|View full text |Cite
|
Sign up to set email alerts
|

Layer-by-layer assembled membranes with immobilized porins

Abstract: With the synthesis and functionalization of membranes for selective separations, reactivity, and stimuli responsive behavior arises new and advanced opportunities. The integration of bio-based channels is one of these advancements in membrane technologies. By a layer-by-layer (LbL) assembly of polyelectrolytes, outer membrane protein F trimers (OmpF) or “porins” from Escherichia coli with a central pore of ~2 nm diameter at its opening and ~0.7 × 1.1 nm at its constricted region are immobilized within the pore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 78 publications
0
20
0
Order By: Relevance
“…Polyethylene glycol (PEG) with molecular weight from 200, 400, 1000, 4000, 10,000, 20,000, 40 kDa were used as feed to determine MWCO values for the different membranes. Since PEGs are linear polymers, the regression model of hydrodynamic radius (nm) and molecular weight (kDa) is given by Equation (4) [ 68 ]: r H = 0.06127 (MW) 0.3931 …”
Section: Methodsmentioning
confidence: 99%
“…Polyethylene glycol (PEG) with molecular weight from 200, 400, 1000, 4000, 10,000, 20,000, 40 kDa were used as feed to determine MWCO values for the different membranes. Since PEGs are linear polymers, the regression model of hydrodynamic radius (nm) and molecular weight (kDa) is given by Equation (4) [ 68 ]: r H = 0.06127 (MW) 0.3931 …”
Section: Methodsmentioning
confidence: 99%
“…used a layer‐by‐layer approach to incorporate OmpF or porins from E. coli into poly (vinylidene fluoride) (PVDF) microfiltration membranes. These membranes provided a rejection of 84% for 0.4 to 1.0 kDa organic molecules and a pH‐dependent salt rejection . Some examples of incorporation of membrane proteins into synthetic systems are listed in Table .…”
Section: Incorporation Of Diffusion Channels Into Synthetic Systemsmentioning
confidence: 99%
“…These proteins can be exploited to synthesize artificial systems for various applications such as voltage gating, pH‐dependent rejections, specific molecular weight cutoff, ion transport, and so forth. . There are some limitations involved in incorporation strategies such as functionality of these proteins, similarity of synthetic system with the natural environment of lipid bilayer in the cell membrane .…”
Section: Incorporation Of Diffusion Channels Into Synthetic Systemsmentioning
confidence: 99%
“…The various samples that were used in this study along with their Stokes-Einstein radii are shown in Table I, where the Stokes-Einstein radii were obtained from literature studies using dynamic slight scattering. [35][36][37][38][39] The rejection values of all solutes were used to determine the MWCO of both unmodified and modified PBI membranes. The molecular weight of solute in feed solution for which the membranes showed more than 90% rejection was considered the MWCO of the membranes.…”
Section: Molecular Weight Cutoffmentioning
confidence: 99%
“…Neutral Solutes Used for MWCO Analysis and their Stokes-Einstein Radii in nm, According to Literature Studies[35][36][37][38][39] …”
mentioning
confidence: 99%